Effect of Cognitive Rehabilitation on Executive Functions in Adolescent Survivors of Leukemia: A Randomized and Controlled Clinical Trial - Omid Amani; Mohammad Ali Mazaheri; Vahid Nejati; Bibi Shahin Shamsian (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective One of the phenomena that have been observed among survivors of childhood cancers like leukemia is the late side effects of the applied treatments, such as chemotherapy, on executive cognitive functions. These problems lead to various complaints such as experiencing dullness while performing activities, encountering difficulties in conducting various tasks simultaneously, and having no interest in laying out plans. These issues will endanger and negate the advantage of any increase in survival rate. Therefore, the aim of this clinical trial is to evaluate the efficiency of using a series of cognitive rehabilitation exercises in improving executive functions on the level of hope in adolescents who survived leukemia.  Methods & Materials This research is a quasi-experimental study with pretest, posttest, and follow-up stages. The study population consisted of all the adolescents between the ages of 12 to 18 years, who survived leukemia, in Tehran city. Purposive sampling method was used. Based on the medical records and inclusion and exclusion criteria, 30 patients, who had been referred to the section of blood diseases at the Mofid hospital in the year 2013, were selected and accidentally classified into intervention (15) and wait list (15) groups. The participants of the intervention group received treatment offered as part of the cognitive rehabilitation program over a period of 12 sessions. The research data was collected using the Wechsler Intelligence Scale, Achenbach Behavior Scale, and the Miller Hope Test. These data were analyzed with the help of descriptive statistics (mean and standard deviation) and inferential statistics (multivariate analysis of covariance). Results The mean treatment duration was found to be 23.27 months in the intervention group and 27.00 months in the waiting list group. The mean treatment completion time of the intervention group is obtained as 25.60, and in the waiting list group as 30.67. The findings of the Miller hope questionnaire revealed that executive functions witnessed a significant positive effect due to cognitive rehabilitation, in adolescents who survived leukemia (P<0.05). This effect remained stable, as shown in a follow-up of one month after the intervention (P<0.05).  Conclusion The results of this study have shown that the effect of cognitive rehabilitation on executive functions reaps significant dividends with regard to the promotion of hope in adolescents who survived leukemia and have been under the chemotherapy. The promotion of hope in participants belonging to the intervention group was more than in the participants of the wait list group. Given the fact that, today, one of the main goals of treatment of chronic diseases such as cancer is to enhance the quality of mental health of the surviving patients, the use of inexpensive and accessible programs like cognitive rehabilitation would be very effective. Consequently, healthcare professionals could attempt to reduce the side effects caused by chemotherapy and radiation, in addition to improving the cognitive issues of affected individuals, by placing emphasis on hope among the concerned patients. Therefore, it is recommended to conduct further research by considering the results of this work in order to develop effective cognitive rehabilitation interventions, thereby, enhancing the coping strategies, quality of life, and mental health of patients who are afflicted with cancer and those who survived cancer. Cognitive rehabilitation services should also be considered for post-treatment follow-up projects.